Chaotic Dynamics and Subharmonic Bifurcation of Charged Dilation-AdS Black Hole in Extended Phase Space Subject to Harmonic Excitation - Qinrui Chen; Liangqiang Zhou; Fengxian An (Physics)
In this paper, the chaotic behavior and subharmonic bifurcation in a dynamical model for charged dilation-AdS black holes are investigated in extended phase space using analytical and numerical methods. An analytical expression for the chaotic critical value at the disturbance amplitude is obtained using the Melnikov method, revealing the monotonicity of the threshold values for chaos with charge and frequency, and the coupling parameters between the expansion field and the Maxwell field are studied. It is shown that chaos can be controlled through the system parameters. Meanwhile, an analytical expression for the critical value of the bifurcation of subharmonic orbits at disturbance amplitudes is acquired using the subharmonic Melnikov method. The relationship between the threshold value and the vibration frequency and the order of the subharmonic orbit is studied. This demonstrates that the system undergoes chaotic motion via infinite odd-order subharmonic bifurcations. Finally, numerical simulations are used to verify the analytical results.